2016
DOI: 10.1007/s00406-016-0679-4
|View full text |Cite
|
Sign up to set email alerts
|

Training in psychiatry throughout Europe

Abstract: Psychiatry is the largest medical specialty in Europe. Despite efforts to bring harmonisation, training in psychiatry in Europe continues to be very diverse. The Union Européenne des Médecins Spécialistes (UEMS) has issued as from 2000 a charter of requirements for the training in psychiatry with an additional European Framework for Competencies in Psychiatry in 2009. Yet these have not been implemented throughout Europe. In this paper, the diversity in training throughout Europe is approached from different a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 29 publications
0
29
0
7
Order By: Relevance
“…An estimated 45% increase in consultant numbers is required by 2033; however, it is predicted that consultant numbers will actually decrease by 7% over this period 4 . These recruitment difficulties are not unique to the UK: similar issues have been described across Europe and the USA 5 . The reasons for this loss of consultant stock are multiple, including the final cohort of those consultants retiring with enhanced pension rights, but there is also a clear trend of decreased training within the specialty.…”
mentioning
confidence: 88%
“…An estimated 45% increase in consultant numbers is required by 2033; however, it is predicted that consultant numbers will actually decrease by 7% over this period 4 . These recruitment difficulties are not unique to the UK: similar issues have been described across Europe and the USA 5 . The reasons for this loss of consultant stock are multiple, including the final cohort of those consultants retiring with enhanced pension rights, but there is also a clear trend of decreased training within the specialty.…”
mentioning
confidence: 88%
“…The structure and content of psychiatry training has been a topic of concern for decades, with a shift from aiming for a common psychiatric training programme throughout Europe to aiming for similar quality of training programmes [11][12]. To ensure the quality of the different training programmes, the European Union of Medical Specialists (UEMS) published The European Framework for Competencies in Psychiatry [13].…”
Section: Introductionmentioning
confidence: 99%
“…This would allow for both psychiatry residents and clinical psychology students to acquire the same level of necessary skills and have access to consistent training focused on providing psychotherapy. Previous research [39,40] has highlighted the importance of learning psychotherapy in psychiatry residency programs, and Kovach et al [39] reported that, despite psychiatry residents typically reporting interest in psychotherapy, there is significant variability in the quality of training opportunities available, necessitating an examination of psychotherapy curricula. Therefore, the standardization and implementation of a consistent curriculum that improves the state of psychotherapy education within Iran is necessary for the field to progress and adequately train new professionals.…”
Section: Discussionmentioning
confidence: 99%